1999
DOI: 10.1542/peds.103.5.e65
|View full text |Cite
|
Sign up to set email alerts
|

The Perceptions and Practices of Pediatricians: Tobacco Intervention

Abstract: Pediatricians are missing opportunities to help their patients to stop smoking and to prevent smoking initiation. Pediatricians are intervening least frequently with parents who smoke. Practices should be tailored to the specific target group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
77
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 47 publications
4
77
0
1
Order By: Relevance
“…Dentists who believed that they were successful in helping patients quit were three times more likely to advise patients to quit (Albert et al, 2005). Zapka et al (1999) found that pediatricians who believed that counseling was effective were more likely to report counseling. In another study, HHC nurses who believed that their counseling would be effective at helping their patients quit were significantly more likely to recommend the use of nicotine replacement, and spent more time counseling patients (Borrelli et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Dentists who believed that they were successful in helping patients quit were three times more likely to advise patients to quit (Albert et al, 2005). Zapka et al (1999) found that pediatricians who believed that counseling was effective were more likely to report counseling. In another study, HHC nurses who believed that their counseling would be effective at helping their patients quit were significantly more likely to recommend the use of nicotine replacement, and spent more time counseling patients (Borrelli et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
“…Self-efficacy to counsel smokers is associated with increased tobacco counseling among physicians (Cabana et al, 2004;Frank, Winkleby, Altman, Rockhill, & Fortmann, 1991;Goldstein et al, 1997;Zapka et al, 1999) and nurses (Borrelli et al, 2001). One cross-sectional study of HHC nurses found that, for every one-point increase in self-efficacy, there was a 30% increase in the odds that nurses would counsel their patients who smoked (Borrelli et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for not addressing tobacco include lack of time and competing priorities, questions concerning reimbursement and treatment efficacy, and lack of preparation and training (Zapka, et al, 1999). The latter is consistent with calls for training medical students and residents in tobacco prevention and control (Fiore, et al, 2004).…”
Section: Introductionmentioning
confidence: 79%
“…While the American Academy of Pediatrics (1998;2001;2005) urges pediatricians to address tobacco, surveys of pediatricians (Hymowitz, 1995;Zapka, et al, 1999;Perez-Stabile, et al, 2001;Bonolllo, et al, 2002;Marlarcher, et al, 2002;Tanski, et al, 2003;Kaplan, et al, 2004), residents (Kenney, et al, 1988;Hymowitz, et al, 2004), patients (Alfano, et al, 2002;Sims, et al, 2004;Hymowitz, et al, 2005a), and parents (Frankowski and Secker-Walker, 1994;Sharif, et al, 2003;Winickoff, et al, 2003a;Hymowitz, et al, 2005b) show that many pediatricians are not meeting the tobacco challenge. Like many other physicians, (e.g., Ferketich, et al, 2006), pediatricians are more likely to ask about tobacco use and exposure and advise change than to provide assistance for modifying behavior (cf.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation